A practical meshfree inverse method for identification of thermo-mechanical fracture load of a body by examining the crack path in the body. (1st December 2021) - Liaghat, F.; Khosravifard, A.; Hematiyan, M.R.; Rabczuk, T.
Abstract: An inverse meshfree approach is presented for thermo-mechanical load identification of a fractured body. To this end, the crack propagation path is used as the input of the inverse analysis. This study can be used for finding the thermo-mechanical loads that have led to the fracture of a body, and is applicable to situations where the direct measurement of the boundary loadings on some part of a body is not possible. This highly ill-posed problem is solved using the meshfree radial point interpolation method (RPIM) with a global optimization approach. The inspected crack path is compared to the one obtained numerically and their difference is set as a cost function. By finding the minimum of this cost function, the actual loading conditions that have led to the fracture of the body is obtained. The density clustering method is used as the global optimization method in which the damped Gauss-Newton technique is used as the local search algorithm. To demonstrate the performance of the presented meshfree inverse approach, two examples are provided.